Functional gains in energy and cell metabolism after TSPO gene insertion. Issue 5 (4th March 2017) - Liu, Guo-Jun; Middleton, Ryan J.; Kam, Winnie Wai-Ying; Chin, David Y.; Hatty, Claire R.; Chan, Ronald H. Y.; Banati, Richard B.
ABSTRACT: Recent loss-of-function studies in tissue-specific as well as global Tspo (Translocator Protein 18 kDa) knockout mice have not confirmed its long assumed indispensability for the translocation of cholesterol across the mitochondrial inter-membrane space, a rate-limiting step in steroid biosynthesis. Instead, recent studies in global Tspo knockout mice indicate that TSPO may play a more fundamental role in cellular bioenergetics, which may include the indirect down-stream regulation of transport or metabolic functions. To examine whether overexpression of the TSPO protein alters the cellular bioenergetic profile, Jurkat cells with low to absent endogenous expression were transfected with a TSPO construct to create a stable cell line with de novo expression of exogenous TSPO protein. Expression of TSPO was confirmed by RT-qPCR, radioligand binding with [3H]PK11195 and immunocytochemistry with a TSPO antibody. We demonstrate that TSPO gene insertion causes increased transcription of genes involved in the mitochondrial electron transport chain. Furthermore, TSPO insertion increased mitochondrial ATP production as well as cell excitability, reflected in a decrease in patch clamp recorded rectified K channel currents. These functional changes were accompanied by an increase in cell proliferation and motility, which were inhibited by PK11195, a selective ligand for TSPO. We suggest that TSPO may serve a range of functions that can be viewed as downstream regulatory effects of its primary, evolutionary conserved role in cell metabolism and energy production.